Effects of Product Quality and Price on the Purchase Decision in Shopee Marketplace (A Case Study at Department of Business Administration, Politeknik Negeri Medan) - Rahmadani Koto; Ocdy Amelia; Cahyo Pramono (Budapest International Research and Critics University, 2022)
Business world in the digital era is developing rapidly today which causes business development increasingly to lead to intense competition. Technological advances make it possible to carry out business relationships through a technological device known as internet. This business activity that utilizes the internet is known as a marketplace. The research entitled